Experimental Study the Effect of Tool Geometry on Dimensional Accuracy in Single Point Incremental Forming (SPIF) Process - Bedan, Aqeel Sabree; Habeeb, Halah Ali (Al-Nahrain Journal for Engineering Sciences, 2018)
Incremental forming is a flexible sheet metal forming process which performed by utilizes simple tools to locally deform a sheet of metal along a predefined tool path without using of dies. One limitations of single point incremental forming (SPIF) process is the error occur between the CAD design and the product profile. This work presents the single point incremental forming process for produced pyramid geometry and studied the effect of tool geometry, tool diameter, wall angle, and spindle speed on the dimensional accuracy. Three geometries of forming tools were used in experimental work: ball end tool, hemispherical tool, and flat with round corner tool. The sheet material used was pure Aluminum (Al 1050) with thickness of (0.9 mm). The experimental tests in this work were done on the computer numerical control (CNC) vertical milling machine. The products dimensions were measured by utilized the dimensional sensor measuring instrument. The extracted results from the single point incremental forming process indicated the best acceptance between the CAD profile and product profile was found with the ball end tool and diameter of (10 mm), wall angle (50°) and the rotational speed of the tool was (800 rpm).